2014
DOI: 10.3947/ic.2014.46.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hand Hygiene Compliance is Associated with the Change of Perception toward Hand Hygiene among Medical Personnel

Abstract: BackgroundHand hygiene compliance has improved significantly through hand hygiene promotion programs that have included poster campaign, monitoring and performance feedback, and education with special attentions to perceived subjective norms. We investigated factors associated with improved hand hygiene compliance, focusing on whether the improvement of hand hygiene compliance is associated with changed perception toward hand hygiene among medical personnel.Materials and MethodsHand hygiene compliance and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 8 publications
5
31
1
2
Order By: Relevance
“…In most studies, hand hygiene adherence of doctors before patient contact was shown to be low [16]. In a similar study, the increase in doctors' hand hygiene adherence by training was more evident compared to other medical personnel [17]. Education level of doctors before starting occupation may have a role in their adoption of the application.…”
Section: Discussionmentioning
confidence: 91%
“…In most studies, hand hygiene adherence of doctors before patient contact was shown to be low [16]. In a similar study, the increase in doctors' hand hygiene adherence by training was more evident compared to other medical personnel [17]. Education level of doctors before starting occupation may have a role in their adoption of the application.…”
Section: Discussionmentioning
confidence: 91%
“…ICNs considered the charge nurse, head nurse, and physician as important role models, apart from colleagues, to improve HH compliance, as in previous studies. 20,21 Infection control experience was significantly associated with HH role model and HH performance of HCWs (significantly lower in groups with < 12 months of experience).…”
Section: Discussionmentioning
confidence: 99%
“…Perception has been identified as a significant predictor of nurses' HH intentions and adherence, 24 as well as HH performance in a previous study conducted in Korea with the same study methods 13 and in other studies. 20,21 Further research needs to be conducted on improving the perception of ICNs.…”
Section: Discussionmentioning
confidence: 99%
“…Hand hygiene adherence has been maintained at approximately 70% for the entire hospital since the fourth quarter of 2010. 22 ASC with preemptive CPs and enhanced EC has been performed for the control of CRAB in the medical ICU since June 2012. We could not cohort patients infected or colonized with CRAB only to designated rooms due to CRAB endemicity in the medical ICU.…”
Section: Discussionmentioning
confidence: 99%